Increasing Vegetable Oil Demand in China: Impacts on the International Soybean Market - Jia, Hongmei; Li, Yanxi; Li, Xiang (Journal of Applied Business and Economics, 2021)
Increases in income and urbanization lead to strong demand for edible oil in China, which impacts global soybean trade. This study reviews the history of China’s soybean industry and vegetable oil consumption patterns, compares the demand for vegetable oil with demand in Japan and South Korea, and then forecasts China’s demand for vegetable oil and soybean imports in the coming decades.